Neutralizing activity against bovine H5N1 HPAIV (clade 2.3.4.4b) in human plasma after seasonal influenza vaccination - Lu Zhang; Georg M. N. Behrens; Amy Kempf; Inga Nehlmeier; Sabine Gärtner; Anna-Sophie Moldenhauer; Luise Graichen; Christine Happle; Michael Winkler; Alexandra Dopfer-Jablonka; Stefan Pöhlmann; Markus Hoffmann (Emerging Microbes and Infections, 2025)
In 2024, a clade 2.3.4.4b H5N1 highly pathogenic avian influenza virus (HPAIV) emerged in dairy cattle in the United States and spread rapidly to over 1,000 herds across multiple states. At least 41 human infections have occurred through contact with infected cattle, though no fatalities have been reported so far. This raises questions about whether the human innate immune system provides a barrier to bovine H5N1 HPAIV and whether seasonal influenza vaccines offer cross-protection. To address these questions, we used pseudoviruses bearing hemagglutinin (HA) and neuraminidase (NA) from seasonal influenza A or various H5Ny HPAIV strains (from cattle, duck, and seal). Pseudoviruses bearing H5N1 HPAIV HA and NA entered a wide range of mammalian and avian cell lines, including multiple cell lines from the human respiratory tract, while entry into A549 human lung cells was reduced when IFITM proteins were expressed. Additionally, preincubation of pseudovirus particles bearing H5N1 HPAIV HA and NA with plasma from individuals vaccinated with seasonal influenza vaccines inhibited viral entry. Collectively, these results suggest that the human innate immune system imposes a barrier against bovine H5N1 HPAIV infection and that seasonal influenza vaccines can induce cross-neutralizing activity against bovine H5N1 HPAIV.